Investigating the Use of Modal Auxiliary Verbs in Tempo Editorial - Azka Saeful Haq (Universitas Veteran Bangun Nusantara, 2020)
Editorial texts provide opinions to influence publics toward actual issues in society. The opinions contain critics served in suitable dictions and argumentations to access wider comprehension toward reality. This research aims to investigate frequency of modal auxiliary verbs in Tempo editorial and the meaning of the frequency. The method used in this research is descriptive qualitative. The data is collected from online Tempo editorial text with the similar national issue. The researcher only chooses 9 texts in November 2019. The result consists of 104 data that is divided into three major types of modal auxiliary verb function, namely prediction, necessity, and probability.Keywords : Modal Auxiliary Verb, Editorial, Prediction, Necessity, Probability